Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
OCLC: 1233305994
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.–publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Section: xv, 240 pages : illustrations ; 22 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé